2013
DOI: 10.1017/s0033291713002389
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in brain structure in adults with anorexia nervosa and the impact of illness duration

Abstract: Findings are in accordance with several previous studies on brain structure and match functional studies that have assessed the symptomatology of anorexia nervosa, such as body image distortion and cognitive bias to food. The correlation with duration of illness supports the implication of cerebellar atrophy in the maintenance of low weight and disrupted eating behaviour and illustrates its role in the chronic phase of anorexia nervosa. The lack of other correlations suggests that these findings are not relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 76 publications
(135 reference statements)
10
80
4
1
Order By: Relevance
“…GM changes in the hypothalamus (Boghi et al, 2011) and the right frontal and temporal cortical structures Amianto et al, 2013); GM changes in the cingulum correlated with lowest lifetime BMI (Muhlau et al, 2007). Still, other studies did not find any correlations of GM changes with BMI (Joos et al, 2010;Fonville et al, 2013). The amount of weight loss prior to admission was associated with global GM loss in one small study (Bomba et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…GM changes in the hypothalamus (Boghi et al, 2011) and the right frontal and temporal cortical structures Amianto et al, 2013); GM changes in the cingulum correlated with lowest lifetime BMI (Muhlau et al, 2007). Still, other studies did not find any correlations of GM changes with BMI (Joos et al, 2010;Fonville et al, 2013). The amount of weight loss prior to admission was associated with global GM loss in one small study (Bomba et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…Several studies have shown the potential clinical significance of acute volume loss in the brains of patients with AN at admission, such as altered visuospatial functioning (CastroFornieles et al, 2009), reduced perceptual organisation and reasoning (McCormick et al, 2008) and increased drive for thinness (Joos et al, 2010). However, these findings have to be regarded as preliminary, as other studies did not find correlations between brain volume changes and clinical measures (Chui et al, 2008;Amianto et al, 2013;Fonville et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…2 Consistent with these data, studies with currently ill patients with anorexia nervosa have shown widespread grey matter decreases in the neocortex and in areas linked to emotion regulation and reward, such as the anterior cingulate, orbitofrontal cortex, insular cortex, hippocampus/ parahippocampus, amygdala and striatum. [4][5][6] However, other studies have reported grey matter increases in neocor tic al [6][7][8] and limbic regions. 7,8 Moreover, although some of these alter ations may normalize in recovered patients, 4 other studies have shown the persistence of volume alterations in recovered patients.…”
Section: Introductionmentioning
confidence: 99%
“…Those affected had significantly lower whole-brain volume, significantly higher volume of cerebrospinal fluid and significantly lower gray matter volume. There was also a negative correlation between duration of illness and gray matter volume [36]. Similarly, there is evidence of focal gray matter atrophy in the cerebellum of patients with anorexia nervosa, which is correlated with disease duration [37].…”
Section: Neurologicmentioning
confidence: 82%